Psychological Problems Arising When Raising Children in an Incomplete Family - Baratova, Dilafruz (Researchparks Publishing, 2023)
the article deals with the psychological problems faced by parents and children in an incomplete family. The main features of raising children in the absence of one of the parents, as well as factors affecting the psychological well-being of children, are described. Modern approaches to the psychological support of children and parents in single-parent families are presented.